PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROBING PROMPTING DAN LEARNING CYCLE 5E - Anita Adinda (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2018)
The purpose of this study was to determine the significant differences between students' mathematical problem solving abilities after using the Probing Prompting model and the Learning Cycle 5E learning model. This research is a quantitative research experiment using quasi experimental design in two different classes which are divided into experimental class I and experimental class II. The population of this study were all eighth grade students of Padangsidimpuan MTs Negeri 2 with sampling using cluster random sampling technique. The class sampled in this study is class VIII-1 as the experimental group I with the treatment of the Probing Prompting learning model and class VIII-3 as the experimental group II with the treatment of the learning model of the Learning Cycle 5E model. The instrument of data collection is a test describing the ability to solve mathematical problems in the subject matter of a circle. Based on normality and homogeneity tests, both classes of samples are normally distributed and homogeneous. Hypothesis testing using the independent samples test obtained a significance value of 0.356, and therefore 0.356> 0.05, there was no significant difference between students' mathematical problem solving abilities in class VIII-1 (experiment I) with problem solving abilities. mathematics students in class VIII-3 (experiment II). This shows that there is no difference in problem solving abilities of students taught using the Probing Promting learning model and the 5E Learning Cycle learning model.